(untitled) (International Journal of Built Environment and Sustainability, 2021)
The public understanding of climate change, methods, mitigation, adaptation and the reason behind it have been investigated in developed countries. The current knowledge levels in the Global South remains limited, this while countries forming part of the Global South are more vulnerable to resultant effects of global warming. This requires the urgent attention by both citizens, who lack relevant information as well as decision makers lacking environmental literacy to establish long-term sustainable strategies. With just 9 years left, the probability of achieving the Sustainable Development Goals (SDGs), is unlikely and will require the complete redevelopment of the building sector. Focusing on the built environment, this paper uses contemporary definitions of the Global South to establish the contribution, significance and lack of energy efficiency mechanisms in the face of climate change. A combination of literature, desk research and data gathering from various sources are employed to establish the contribution of the Global South built environment to climate change. Using Carbon Dioxide (CO₂) emissions, 2050 urban population figures and distinctive climatic regions as basis, this study selected the largest role players to establish the status, extent and efficacy of building energy codes. The review point towards a built environment lacking the necessary building energy codes, with approximately 47% of selected Global South countries not implementing any form of building energy efficiency regulations or related policies. As part of the recommendations, Global South countries lacking the necessary regulations are encouraged to revise, update or adopt possible best practice standards from relevant countries that implement mandatory building energy codes. This study aims to address the gap in knowledge, establish a way forward and facilitate a larger implementation of building energy codes and strategies in the Global South